A children's bible [compact disc, unabridged] : a novel - Millet, Lydia, 1968- (Dreamscape Media, LLC, 2020)
This indelible novel of teenage alienation is a prophetic, heartbreaking story of generational divide, and a haunting vision of what awaits on the far side of Revelation.